The Constitutional Position of the Public Prosecutor’s Office in Implementing Restorative Justice: A Constitutional Law Perspective and the Concept of Maslahah in Fiqh Siyasah - Faizal, Reza; Holijah, Holijah; Bukhari, K.A. (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This research examines the position and authority of the Indonesian Prosecutor's Office in implementing the Restorative Justice (RJ) mechanism as a legal breakthrough in the criminal justice system. The paradigm shift from retributive to restorative justice, implemented through the Indonesian Prosecutor's Regulation Number 15 of 2020, raises fundamental questions regarding its constitutional basis and philosophical legitimacy. This thesis analyzes this issue from two main perspectives: Constitutional Law (Hukum Tata Negara - HTN) and the concept of Maslahah in Fiqh Siyasah (Islamic Political Jurisprudence). From the perspective of Constitutional Law, the implementation of RJ by the Prosecutor's Office is a manifestation of the Prosecutor General's asas oportunitas (discretionary principle) as regulated by law. However, this discretion must operate within the constitutional framework and the principles of a rule of law state, ensuring that the termination of prosecution does not violate victims' rights and guarantees legal certainty. The HTN analysis focuses on the extent to which the Prosecutor's Regulation possesses binding legal force and how mechanisms of control and accountability are applied to prevent the abuse of authority. Meanwhile, from the Fiqh Siyasah perspective, the concept of Restorative Justice aligns with the principle of Maslahah (public interest/welfare). The RJ approach, which prioritizes the restoration of relationships, reconciliation, and the prevention of greater negative impacts (mafsadah) resulting from formal judicial processes, substantially fulfills the objectives of Sharia (maqashid sharia), namely the preservation of life (hifzh an-nafs) and property (hifzh al-mal). The implementation of RJ by the Prosecutor's Office, by prioritizing peaceful settlements for minor cases, is considered a siyasah syar'iyyah (Sharia-compliant policy) aimed at achieving public welfare. This research concludes that the position of the Prosecutor's Office in implementing Restorative Justice possesses dual legitimacy: juridical-constitutional as the execution of structured discretion, and philosophical-theological as an effort to realize Maslahah in law enforcement. The synchronization of these two reviews confirms that the Prosecutor's RJ policy is a progressive step towards substantive justice oriented towards social restoration. [Penelitian ini mengkaji kedudukan dan kewenangan Kejaksaan Republik Indonesia dalam menerapkan mekanisme Keadilan Restoratif (Restorative Justice/RJ) sebagai terobosan hukum dalam sistem peradilan pidana. Pergeseran paradigma dari keadilan retributif menuju restoratif, yang diimplementasikan melalui Peraturan Kejaksaan Republik Indonesia Nomor 15 Tahun 2020, menimbulkan pertanyaan mendasar mengenai landasan konstitusional dan legitimasi filosofisnya. Tesis ini menganalisis isu tersebut dari dua perspektif utama: Hukum Tata Negara (HTN) dan konsep Maslahah dalam Fiqh Siyasah. Dari tinjauan Hukum Tata Negara, penerapan RJ oleh Kejaksaan merupakan manifestasi dari asas oportunitas (diskresi) Jaksa Agung yang diatur dalam undang-undang. Namun, diskresi ini harus berada dalam koridor konstitusi dan prinsip negara hukum, memastikan bahwa penghentian penuntutan tidak melanggar hak-hak korban dan menjamin kepastian hukum. Analisis HTN berfokus pada sejauh mana Peraturan Kejaksaan tersebut memiliki kekuatan hukum yang mengikat dan bagaimana mekanisme kontrol dan akuntabilitas diterapkan untuk mencegah penyalahgunaan wewenang. Sementara itu, dari perspektif Fiqh Siyasah, konsep Keadilan Restoratif selaras dengan prinsip Maslahah (kemaslahatan umum). Pendekatan RJ yang mengutamakan pemulihan hubungan, rekonsiliasi, dan pencegahan dampak negatif (mafsadah) yang lebih besar akibat proses peradilan formal, secara substansial memenuhi tujuan syariat (maqashid syariah), yaitu memelihara jiwa (hifzh an-nafs) dan harta (hifzh al-mal). Penerapan RJ oleh Kejaksaan, dengan memprioritaskan penyelesaian damai untuk perkara ringan, dianggap sebagai kebijakan siyasah syar'iyyah yang bertujuan mencapai kemaslahatan publik. Penelitian ini menyimpulkan bahwa kedudukan Kejaksaan dalam menerapkan Keadilan Restoratif memiliki legitimasi ganda: yuridis-konstitusional sebagai pelaksanaan diskresi yang terstruktur, dan filosofis-teologis sebagai upaya mewujudkan Maslahah dalam penegakan hukum. Sinkronisasi kedua tinjauan ini menegaskan bahwa kebijakan RJ Kejaksaan adalah langkah progresif menuju keadilan substantif yang berorientasi pada pemulihan sosial.]